Pathways out of poverty in western Kenya and the role of livestock - Kristjanson, Patricia M.; Krishna, A.; Radeny, Maren A.O.; Nindo, W. (Food and Agriculture Organization of the United Nations, 2004)
A community-based methodology called the ‘stages of progress’ approach was used to assess household poverty dynamics in 20 communities and for over 1,700 households representing two different ethnic groups in Western Kenya. The objectives of the study were to obtain a better understanding of households’ pathways into, and out of, poverty, with poverty defined from the communities’ own perspective. The proportion of households that have managed to escape poverty over the last 25 years was ascertained, as well as the proportion of households that have fallen into poverty during the same period. The major reasons for movements into or out of poverty were elicited at both the community and household-level, and in particular, the role that livestock play in the different pathways was examined.Ten communities in Vihiga District and ten in Siaya District were included in the study. Vihiga District (Western Province), with an extremely high population density of 886 persons per square km, has seen average farm sizes steadily declining to a current 0.5 ha. Poverty rates here are amongst the highest in Kenya, rising from 53 percent in 1994 to 58 percent in 1999. HIV prevalence rates rose from 12 percent in 1994 to 25 percent in 2000. In Siaya District (Nyanza Province), with a lower population density of 316 persons per square km, 47 percent of the population fell below the rural poverty line in 1994, increasing to 64 percent in 1999. While average farm sizes are higher in Siaya, most of them are located on lower potential agricultural land than that found in Vihiga. Most of Siaya’s population depends on small-scale agriculture (mainly subsistence crop farming), local businesses, livestock production and fishing. Siaya has the highest levels of HIV prevalence and HIVrelated sickness and death rates in Kenya, rising from 14 percent in 1994 to 27 percent in 2000. Key to the approach used was to define with the participating communities a common understanding of poverty. What, for example, does an extremely poor household do when a little bit of money becomes available to the household? Which expenses are usually the first to be incurred? As a little more money flows in, what does this household do in the second stage? The third stage? And so on. Discussions of these questions provoked lively debate among assembled villagers followed by high levels of consensus as to the successive stages of household progress from acute poverty to economic self-reliance. Most interesting was the broad agreement across nearly all villages on the sequence of these stages. The results show that households, as they climb out of poverty, typically first acquire food, then (in the following order) clothes, shelter, primary education for their children, and small animals including chickens, sheep and goats. Beyond these initial stages of progress, households are no longer considered poor. A remarkably similar understanding of poverty exists within the different villages and across the two main ethnic groups found in Vihiga and Siaya Districts of western Kenya. In almost all the villages, purchasing local cattle came in the first stage beyond the poverty threshold drawn by the villagers. Community members were then asked to describe each current household in the village in terms of whether they were above or below that poverty line 25 years ago (a full generation) and today. The Pathways out of Poverty in Western Kenya and the Role of Livestock 2 reasons why particular households had moved into or out of poverty were discussed at the community-level and followed up in more detail with individual households. The field researchers conducting this study received considerable facilitation training towards delving in detail into the reasons, many of which are ‘nested’ or linked, for household movements into and out of poverty. The results show considerable movement over the last 2½ decades by households in this region both into and out of poverty, and the main reasons behind households’ escape from poverty are completely different (i.e. not merely the opposite) from the reasons for descent into poverty, and hence have different policy implications. In Vihiga District, 27 percent of households managed to escape from poverty in the last 25 years, while 11 percent fell into poverty at the same time. In Siaya District, only 8 percent of households managed to climb out of poverty, while 29 percent became impoverished during the same period. A similar set of reasons for these movements, while varying slightly from village to village, was found to be broadly shared among all the study villages. Most households (73 percent) in both districts that escaped poverty over the last 25 years did so because they diversified their income sources when a household member obtained a job in the urban formal or informal sector. Over 80 percent of these jobs (accounting for a total of 61 percent of successful escapes) were found within the private sector. Of the households that escaped poverty, a major reason for 57 percent of those that did so was by diversifying on-farm income through cash crop production. These households were able to produce and consistently sell either surplus food crops (sorghum, maize, bananas) or cash crops (tea, sugarcane, rice). In 42 percent of the cases, households that had escaped poverty diversified their on-farm incomes through livestock, ranging from poultry to dairy animals. Diversification of income sources through livestock farming emerged as a particularly important strategy for escaping poverty in Vihiga District. Poor health and health-related expenses were the principal reasons overwhelmingly cited as responsible for households declining into poverty in both Districts (cited by 73 percent of households that had fallen into poverty). Following these were heavy funeral expenses, particularly the slaughter of a household’s livestock assets, mentioned in 63 percent of the cases. Over half of households cited low levels of education within the household as another critical factor in explaining why they became poor. The striking importance of health and health-related problems and expenses in poverty status is also seen in India and in other areas of western Kenya and Tanzania. The devastating loss of livestock assets due to funerals is also found in other African countries such as Madagascar and Zambia. And the critical importance of non-farm income diversification in pathways out of poverty has been highlighted in many other studies across Africa. The findings of this study have implications in terms of what has been referred to as ‘cargo net’ versus ‘safety net’ interventions. Cargo nets help poor people climb out of poverty; safety nets stop people from falling into poverty. Redistributive programs to build up the assets of poor people (such as giving heifers to poor households) may be effective in achieving long-term reductions in chronic poverty, but will have to be complemented by safety net policies. The results of the study suggest that the most important safety nets required by poor households in western Kenya are those that help protect the health and improve the education of community members. This study has highlighted the key role that livestock play in both pathways into and out of poverty. On-farm diversification of income sources away from a sole reliance on crops through investment in chickens, sheep, goats and/or cattle helped many of the households in the study escape poverty. Given that investment in large animal stock is typically beyond the means of the poorest households, this finding suggests that projects that provide a heifer or a loan to buy a sheep or goat, for example, could provide a one-time transfer sufficiently substantial to help households lift themselves out of poverty. Such livestock acquisitions, however, must be accompanied by policies and interventions that reduce the risks associated with keeping farm animals alive and productive in Pathways out of Poverty in Western Kenya and the Role of Livestock 3 harsh environments. And without safety net strategies aimed at the huge health and education constraints facing these communities, livestock-related investment strategies may well fail. To open up opportunities for poor households to benefit from livestock even more than they do now, problems of poor roads and market infrastructure, widespread insecurity and high and multiple animal disease risks will have to be addressed. The potential for dairy enterprises in particular would be much larger if some of these risks were lowered. These are areas where local, regional and national authorities have an obvious role to play. Improving access to appropriate information regarding livestock management and disease strategies is an area where research organisations can help.